Studies on Anti-Inflammatory and General Glucocorticoid Physiology in Skeletal Muscles Affected by Duchenne Muscular Dystrophy: An approach towards Exploration of Steroid-Sparing Agents - Herbelet, Sandrine; Rodenbach, Arthur; Paepe, Boel De; Bleecker, Jan L. De (Current Advances in Chemistry and Biochemistry Vol. 7, 2021)
In Duchenne muscular dystrophy (DMD), the activation of proinflammatory and metabolic cellular pathways in skeletal muscle cells is an inherent characteristic. The absence of dystrophin, the protein providing a link between the extracellular matrix and the myocyte cytoskeleton, destabilizes the dystrophin-associated protein complex, a large transmembrane protein complex that acts as a shock absorber during muscle contraction, a receiver and transducer of cellular signals and as a scaffold for signaling proteins. Synthetic glucocorticoid intake counteracts the majority of these mechanisms. However, glucocorticoids induce burdensome secondary effects, including hypertension, arrhythmias, hyperglycemia, osteoporosis, weight gain, growth delay, skin thinning, cushingoid appearance, and tissue-specific glucocorticoid resistance. Hence, lowering the glucocorticoid dosage could be beneficial for DMD patients. A more profound insight into the major cellular pathways that are stabilized after synthetic glucocorticoid administration in DMD is needed when searching for the molecules able to achieve similar pathway stabilization. This review provides a concise overview of the major anti-inflammatory pathways, as well as the metabolic effects of glucocorticoids in the skeletal muscle affected in DMD. The known drugs able to stabilize these pathways, and which could potentially be combined with glucocorticoid therapy as steroid-sparing agents, are described. This could create new opportunities for testing in DMD animal models and/or clinical trials, possibly leading to smaller glucocorticoids dosage regimens for DMD patients.